Potensial Ekspor Komoditas Kopi Dari Indonesia Ke Malaysia Dan Singapura - Raden Jhonny Hadi Raharjo; Zaidan Abdillah Alfianto (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2023)
In the current era of development, there are many sectors that will be made efforts to improve their quality and quality. This is of course to increase output so that it can produce more than expected with the best quality so that it has a decent export value in the international market. Among the many commodities that Indonesia can produce, one that is expected to increase export value is coffee. Indonesia is the fourth largest coffee exporter in the world after Brazil, Vietnam and Colombia in the previous position. Therefore, the coffee commodity is considered feasible and able to contribute to state income. So far, only a small portion of the coffee produced by Indonesia is consumed domestically, while most of it is exported abroad. For countries that geographically tend to be closer to Indonesia, they choose to import coffee commodities from Indonesia, namely Malaysia and Singapore, which are countries that have previously imported coffee from Indonesia in quite large quantities. Therefore, this research will examine the response of coffee export offers from Indonesia to Malaysia and Singapore.